Principal's Edge, The. - Mc Call, Jack (Taylor and Francis, 2013)
Filled with wisdom and inspiration to help you become a better school leader, this book shows you how to transform your school into a Learning Organization. It clarifies and expands the first nine domains of knowledge and skills recommended by the National Policy Board.